2007
DOI: 10.1016/j.bbabio.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of bicarbonate against extraction of the extrinsic proteins of the water-oxidizing complex from Photosystem II membrane fragments

Abstract: A protective effect of bicarbonate (BC) against extraction of the extrinsic proteins, predominantly the Mn-stabilizing protein (PsbO protein), during treatment of Photosystem II (PS II) membrane fragment from pea with 2 M urea, and at low pH (using incubation in 0.2 M glycine-HCl buffer, pH 3.5 or 0.5 M citrate buffer, pH 4.0-4.5) was detected. It was shown that the extraction of the proteins with Mw 24 kDa (PsbP protein) and 18 kDa (PsbQ protein) by the use of highly concentrated solutions of NaCl does not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In this case, the structure of bicarbonate does not necessarily change before and after proton release. Probably, bicarbonate plays major roles in the photoassembly process of the Mn cluster as a ligand to its precursor ,,, , and stabilization of the Mn cluster through an indirect interaction by binding at PsbO or some site in PSII proteins ,, .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the structure of bicarbonate does not necessarily change before and after proton release. Probably, bicarbonate plays major roles in the photoassembly process of the Mn cluster as a ligand to its precursor ,,, , and stabilization of the Mn cluster through an indirect interaction by binding at PsbO or some site in PSII proteins ,, .…”
Section: Resultsmentioning
confidence: 99%
“…Since 1995, various data have been accumulated showing that bicarbonate is indeed functional in oxygen evolution (9,10,12,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In addition to the earlier proposal of a catalytic intermediate (15,16,36), it has been suggested that bicarbonate functions as a ligand to the Mn cluster or an integral cofactor of OEC (20,24,26,33), a cofactor crucial in the photoassembly process of the Mn cluster as a transient ligand to Mn ions (20,21,25,(27)(28)(29)(30)(31)35), a proton transfer mediator bound to a residue in the vicinity of the Mn cluster (32), and an element to indirectly stabilize OEC by binding to PSII proteins or extrinsic proteins (20,21,34). In fact, the X-ray structure by Ferreira et al (4) at 3.5 Å resolution tentatively assigned a part of the nonprotein density to bicarbonate as a ligand bridging Mn and Ca ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation